Behaviour change techniques to optimise participation in physical activity or exercise in adolescents and young adults with chronic cardiorespiratory conditions: a systematic review. Issue 10 (10th October 2019) - Sawyer, Abbey; Lewthwaite, Hayley; Gucciardi, Daniel F.; Hill, Kylie; Jenkins, Sue; Cavalheri, Vinicius
Abstract: Participation in regular physical activity decreases the risk of developing cardiometabolic disease. However, the proportion of people who participate in the recommended amount of physical activity is low, with common barriers including competing interests and inclement weather. In people with chronic cardiorespiratory conditions, participation in physical activity is reduced further by disease‐specific barriers, time burden of treatment and unpleasant symptoms during physical activity. Addressing these barriers during adolescence and early adulthood may promote greater physical activity participation into older age. The aim of this review was to classify interventions aimed at optimising participation in physical activity as 'promising' or 'not promising' in people aged 15–45 years with chronic cardiorespiratory conditions and categorise the behaviour change techniques (BCT) within these interventions. Nine databases and registries were searched (October 2017) for studies that reported objective measures of physical activity before and after an intervention period. Interventions were classified as 'promising' if a between‐group difference in physical activity was demonstrated. Michie et al .'s (2013) v1 Taxonomy was used to unpack the BCT within interventions. Across the six included studies ( n = 396 participants), 19 (20%) of 93 BCT were described. The interventions of three studies were classified as 'promising'. The most commonly used BCT comprised goal setting, action planning and social support. Five BCT were solely used in 'promising' interventions. Our review demonstrated that only 20% of BCT have been utilised, and those BCT that were used only in 'promising' physical activity interventions in adolescents and adults with chronic cardiorespiratory conditions were isolated.